Further evidence on mandatory partner rotation and audit pricing: a supply‐side perspective. (7th April 2017) - Ferguson, Andrew; Lam, Peter; Ma, Nelson
Abstract: This study examines effects of mandatory partner rotation (MPR) on audit fees of Australian‐listed companies. Using a fee changes approach, evidence of fee increases in year of the MPR driven by smaller offices of non‐Big 4 auditors is found, consistent with supply‐side resource constraint arguments. Broadly consistent findings are observed using a fee levels approach. Appointment of inexperienced partners to MPR engagements has no discernible effect on fees. Additional analysis of audit reporting lag indicates fee increases reflect additional audit effort as opposed to a pricing strategy. Overall, the evidence supports recent moves by policy‐makers to soften MPR requirements.